An Exploratory Study Of Work Life Balance Emanates And Work Satisfaction In Ericsson Company-Chennai City (International Journal of Scientific Research and Management (IJSRM), 2015)
In terms of Indian perspective, the anxiety over work-life balance is progressively becoming a common talk especially for telecom employees. Work life balance is condition of equilibrium in which the demand of both professional and personal life is equal. Managing rising demands from the work and family domains represented a source of high strain for many employees which even lead to the health problems among employees. Although it is believed that work family role strain is more common among telecom employees, especially men experience stress resulting from differing roles and demands. The purpose of this paper is to figure out the working atmosphere of Ericsson Company and what is the opinion of employees about the allegiance to work and flexibility on work schedule pertaining to the work life and work satisfaction. We propose that Work-Life Balance is nowadays, no doubt a major concern to be discussed as a serious matter and has to be managed